2020
DOI: 10.1055/s-0040-1719083
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Unfractionated Heparin in Severe COVID-19: An Observational Study of Patients on CRRT and ECMO

Abstract: Objective Severe cases of coronavirus disease 2019 (COVID-19) can require continuous renal replacement therapy (CRRT) and/or extracorporeal membrane oxygenation (ECMO). Unfractionated heparin (UFH) to prevent circuit clotting is mandatory but monitoring is complicated by (pseudo)-heparin resistance. In this observational study, we compared two different activated partial thromboplastin time (aPTT) assays and a chromogenic anti-Xa assay in COVID-19 patients on CRRT or ECMO in relation to their UFH dosages and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
(23 reference statements)
0
28
0
2
Order By: Relevance
“…Anti-Xa activity was determined using an LMWH calibration line (aXa-LMWH; Hyphen Biomed). UFH activity was subsequently calculated with a previously determined formula: UFH anti-Xa = 1.55 * LMWH anti-Xa ( 26 ). Bilirubin (Bilirubin Total, third-generation; Roche Diagnostics, Basel, Switzerland) and creatinine (Enzymatic Reagent; Roche Diagnostics) were determined in serum on a COBAS® 8000 (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-Xa activity was determined using an LMWH calibration line (aXa-LMWH; Hyphen Biomed). UFH activity was subsequently calculated with a previously determined formula: UFH anti-Xa = 1.55 * LMWH anti-Xa ( 26 ). Bilirubin (Bilirubin Total, third-generation; Roche Diagnostics, Basel, Switzerland) and creatinine (Enzymatic Reagent; Roche Diagnostics) were determined in serum on a COBAS® 8000 (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Some authors suggested that these bleeding events might result from worsening COVID-19-associated coagulopathy during ECMO support, further leading to disseminated intravascular coagulation, enhanced fibrinolysis or acquired von Willebrand syndrome, or from heparin overdose. 14 However, data on the kinetics of coagulation and fibrinolysis markers over the course of vv-ECMO in COVID-19 patients which might support this hypothesis are scarce [15][16][17][18][19] and direct comparisons with non-COVID-19 patients are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-Xa (aXa) test samples were diluted (1 unit sample: 2 units pooled reference plasma) and determined using a LMWH calibration line (Biophen LMWH calibrator; Hyphen Biomed). For UFH a previously determined correction factor was applied: aXa-UFH = 1.55 ∗ aXa-LMWH [ 18 ].…”
Section: Methodsmentioning
confidence: 99%